2007
DOI: 10.1074/jbc.m609744200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a HoxA10 Activation Domain Necessary for Transcription of the Gene Encoding β3 Integrin during Myeloid Differentiation

Abstract: Transcription of the ITGB3 gene, which encodes ␤3 integrin, increases during myeloid differentiation. ␣v␤3 integrin mediates adhesion to fibronectin or vitronectin and regulates various aspects of the inflammatory response in mature phagocytes. In these studies, we found that the homeodomain transcription factor HoxA10 interacted with a specific ITGB3 cis element and activated transcription of this gene during myeloid differentiation. We also found that increased fibronectin adhesion in differentiating myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
71
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 37 publications
6
71
0
Order By: Relevance
“…We also found that HoxA10 activates ITGB3 transcription in myeloid progenitor cells and differentiating phagocytes (the gene encoding ␤3 integrin) (20). Our studies suggested that increased ␣v␤3 integrin in HoxA10-overexpressing myeloid progenitor cells facilitated expansion of these cells via interaction with vitronectin and fibronectin in bone marrow stroma.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…We also found that HoxA10 activates ITGB3 transcription in myeloid progenitor cells and differentiating phagocytes (the gene encoding ␤3 integrin) (20). Our studies suggested that increased ␣v␤3 integrin in HoxA10-overexpressing myeloid progenitor cells facilitated expansion of these cells via interaction with vitronectin and fibronectin in bone marrow stroma.…”
supporting
confidence: 57%
“…Our studies suggested that increased ␣v␤3 integrin in HoxA10-overexpressing myeloid progenitor cells facilitated expansion of these cells via interaction with vitronectin and fibronectin in bone marrow stroma. Increased ␣v␤3 integrin expression on HoxA10-overexpressing myeloid progenitor cells leads to an increase in activation of Syk protein-tyrosine kinase, substantiating this hypothesis (20).…”
supporting
confidence: 57%
“…The HoxA9 cDNA was generated by reverse transcription and PCR from U937 cells as described (37). These cDNAs were subcloned into the mammalian expression vector pcDNAamp (Invitrogen) and the murine retroviral vector pMSCVpuro (Clontech, Mountain View, CA), as described (21,22). A vector with the Mll-Ell fusion protein was obtained from D. E. Zhang (University of California, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Oligonucleotides probes were prepared, and DNA binding was analyzed by electrophoretic mobility shift assay (EMSA) and DNA affinity purification techniques as described (18,(21)(22)(23)(24)(25)(26). For EMSA, antibody to HoxA9 or HoxA10 (or irrelevant control antibody) was included in binding assays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation